Respiratory physiotherapy in the bronchiectasis guidelines: is there a loud voice we are yet to hear?. Issue 3 (28th September 2019) - Spinou, Arietta; Chalmers, James D.
Bronchiectasis is a chronic respiratory disease of airway dilatation, where patients typically suffer from respiratory infections, fatigue, sputum, cough, dyspnoea and poor quality of life [1, 2]. This condition has received increased interest over the past years, with important developments in establishing national and international patient registries [3–5], randomised controlled trials of new treatments [6–8] and disease-specific health status questionnaires, such as the Bronchiectasis Health Questionnaire and the Quality of Life Questionnaire – Bronchiectasis [9, 10]. A number of new treatment approaches have been proposed including long term antibiotic therapies and immune modulating drugs [6, 7, 11, 12]. A call for action for great awareness and research into airway clearance techniques and pulmonary rehabilitation in bronchiectasis http://bit.ly/2L8F4Va